The study of facilities management at public hospitals / Rafizza Ahmad - Ahmad, Rafizza (Faculty of Architecture, Planning and Surveying, 2013)
Services and facilities are an important aspect in our daily lives. There are many facilities and services provided that we always used, however, the most important services that is related with our lives are medical services. Hospitals are built in order to help people in the country to stay healthy in terms of solving many health problems. Generally, hospital are not only focusing on the physical facilities only, it is also must including.man other aspect of the services. The definitions of facilities need to be explored and focus more, in order to achieve the maximum level of users’ satisfaction. This is also important to measure the quality of facilities management performance, the study was done to identify the scope of work of facilities management at public hospital specifically and also to measure the users’ satisfaction on their performance, the study are focusing the government hospital which have a different company of facilities management. Normally, government hospitals are appoint a private company which is to be their concession company especially for facilities management. A study was conducted by using questionnaire distribution to visitors and administration staff in the hospitals. Other method that is used is interviewing the facilities management manager, who is responsible to know their scope of work and apply it to the facilities and services work. The results showed that quality of service and facilities management in government hospitals still not reach the level of excellence and should be further improved. In addition, the concession company need to done their work properly by following the Ministry of Health (MoH) guideline and requirements. Thus in overall results of both studies found that hospitals need to overcome problems that cause dissatisfaction to visitors to make both hospitals achieve the level of excellence.